KUSTOMFEST 2024: A Curatorial Study Through the Approach of the Creative Economy - I Made Agus Tresna Tanaya; Muhammad Agil; R. Nur Fathoni Ahmadi; Mikke Susanto (TUMATA: Journal of Arts and Cultural Management, 2025)
The rapid development of the creative economy in Indonesia has fostered the emergence of diverse cultural practices that integrate both aesthetic expression and economic potential. Among these, festivals have become strategic arenas for showcasing creative works while simultaneously generating cultural and commercial value. One notable example is Kustomfest, an annual custom automotive festival held in Yogyakarta, which functions not only as an exhibition space but also as a vital node within the local and regional creative economy ecosystem. This study aims to examine the curatorial strategies employed in Kustomfest 2024 and to assess their contribution to value creation in the creative economy sector. Using a qualitative case study approach, data were collected through in-depth interviews, participant observation, and document analysis involving festival curators, creative practitioners, local business actors, and audiences. The findings reveal that curatorial practices in Kustomfest encompass rigorous selection based on originality, a scrutineering process that ensures functionality and safety, professional documentation for archival and promotional purposes, and independent judging guided by international standards. Furthermore, curators are instrumental in shaping narrative frameworks, enhancing visitor engagement, and connecting creators with market opportunities. Beyond artistic curation, Kustomfest generates significant economic impact, particularly in supporting the growth of MSMEs in the surrounding area. This case illustrates how curatorship can serve as a multidimensional tool for cultural production, audience development, and sustainable economic advancement within Indonesia’s creative industries.